The Influence of Self-Confidence and Vocabulary Mastery on the Speaking Skills of Ninth Grade Students at MTs Al Zaytun - Mufrihani, Nurul; Royani, Ahmad (INCARE, International Journal of Educational Resources, 2025)
Speaking skill is one of the important stages in Arabic language learning which is influenced by students' psychological readiness and vocabulary understanding. This study aims to reveal the relationship between self-confidence, vocabulary understanding, and students' speaking skills. The research used quantitative method with correlation study approach, using Pearson Product Moment data analysis. The research subjects were ninth grade students of Madrasah Tsanawiyah Pondok Pesantren Al-Zaytun, with a sample of 231 students taken using the Slovin formula. Data were collected through a self-confidence questionnaire, vocabulary comprehension test, and speaking skill test. The analysis results showed a significant positive relationship between self-confidence (r = 0.411) and vocabulary comprehension (r = 0.251) to speaking skills. These two variables together contributed greatly to the development of students' speaking skills in Arabic. The findings suggest that self-confidence and vocabulary comprehension can be important indicators in improving students' speaking skills, as well as a basis for the development of more effective Arabic language learning methods.